2020
DOI: 10.2147/opth.s236114
|View full text |Cite
|
Sign up to set email alerts
|

<p>Corneal Hysteresis as a Biomarker of Glaucoma: Current Insights</p>

Abstract: The diagnosis and management of glaucoma has long been dependent on making decisions based on family history, optic nerve head evaluation, intraocular pressure, visual field testing, and optical coherence testing. Other pieces to aid in understanding glaucoma have presented throughout the years, including the role of corneal thickness. The discussion and debate on the mechanism of glaucoma have been attributed to resistance at the level of the conventional outflow pathway, perfusion pressure to the optic nerve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 27 publications
1
14
0
3
Order By: Relevance
“…Congdon and colleagues 13 first showed that CCT and CH are both associated with development of POAG. This new finding was further confirmed by several follow up studies 14 17 . A recent study suggests that CH may predict visual field progression in suspected eyes with apparently well-controlled IOP 18 .…”
Section: Introductionsupporting
confidence: 64%
“…Congdon and colleagues 13 first showed that CCT and CH are both associated with development of POAG. This new finding was further confirmed by several follow up studies 14 17 . A recent study suggests that CH may predict visual field progression in suspected eyes with apparently well-controlled IOP 18 .…”
Section: Introductionsupporting
confidence: 64%
“…Corneal biomechanics is a subject of tremendous clinical research interest in modern ophthalmology. Knowledge of corneal biomechanics is useful in several clinical applications, including management of glaucoma and ectasia risk profiling (Esporcatte et al, 2020;Zimprich et al, 2020). The integration of tomographic and biomechanical data has demonstrated potential to improve the accuracy of detection of ectatic disease and identify susceptibility to develop this complication after laser vision correction (Ambrósio et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, tissues with high CH can absorb energy efficiently and do not deform as much. Eyes with lower CH are more prone to glaucomatous damage of the optic nerve as the connective tissue around it deforms significantly (compared to eyes with high CH) as a result of the effect of the IOP and this can lead to damage of optic nerve fibers that run through the LC [ 20 ].…”
Section: Discussionmentioning
confidence: 99%